Physiological and Anatomical Responses of Red onion (Allium cepa L.) to Drought Stress after Biofertilizer Application - Lestari, Nurrisma Ika; Siswanti, Dwi Umi (Jurnal Biodjati, 2024)
Red onion (Allium cepa) is a plant that requires sufficient water and is susceptible to drought stress. The use of biofertilizer is employed because it contains microorganisms that enhance nutrient availability and assist plant growth under abiotic stress conditions. This study aims to analyze the physiological and anatomical responses of red onion bulbs following the application of biofertilizer under drought stress. The doses of biofertilizer used were 0; 10;15; and 20 L/ha with field capacity levels of 25; 50; 75 and 100%. The parameters tested were bulb diameter, reducing sugar content number of bulb layers, anatomy of root cortex thickness, anatomy of root metaxylem diam Red onion eter, and fresh weight of red onion roots. The method used in determining the level of reducing sugar is the Nelson-Somogyi method. The method used for preparing the red onion root specimens was the embedding method. The results showed that the largest red onion bulb diameter was obtained from treatment A1B2, without the addition of biofertilizer at 75% field capacity. Meanwhile, the highest reduced sugar content was found at a dose of 15 L/ha with 50% field capacity